Rancang Bangun Sistem Informasi Penjualan Pada Perusahaan Kerupuk UD. Rohmat Jaya - Rizki Mentari Timur; A.B Tjandrarini; Pantjawati Sudarmaningtyas (Jurnal Sistem Informasi dan Komputerisasi Akuntansi (JSIKA), 2018)
UD. Rohmat Jaya is a manufacturing company who produces crackers in Sidoarjo, East Java. Sales system at these companies is make to order, the order will be made if there is demand from customers. Based data on January – May 2013 showed that the sales was decline. To determine the cause of declining sales, required evaluation by the leader. For evaluation, company leaders need informations. But the company did not have sufficient sales data and poor data management, so it can not produce useful information for the leader. Based on these problems, then UD. Rohmat Jaya need an information system sales according to the conditions of the company. This information system created by the waterfall method. Steps being taken are interviews and field observations, identification of problems and solutions, planning, analysis and design, coding, and testing. This sales information system can help the leader in providing information that is useful in sales evaluation. Information is provided in report which are prioritized customers, customers decreasing in order, customers who are no longer do the order, the number of receivable per customers, receivable due per period, and development of sales